2018
DOI: 10.17532/jhsci.2018.191
|View full text |Cite
|
Sign up to set email alerts
|

Government and school community member perception on childhood obesity prevention in the primary school settings of Brunei Darussalam

Abstract: Introduction: Childhood obesity is increasing in the Southeast Asian region, including in the nation of Brunei Darussalam. Within the public health focus on obesity prevention, specific settings, including primary schools, have been singled out as suitable sites for action. Recognizing that stakeholders are, in their various roles, producers of policy or implementers of practice, the purpose of this study in Brunei was to establish a baseline for interventions as well as to establish strengths and limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…This review draws on the findings of 22 studies with a total of 1,039 participants. Studies have been performed on different settings of healthcare centers ( n = 5) ( 48 , 50 , 55 , 56 , 60 ), schools ( n = 8) ( 39 , 49 , 51 , 53 , 54 , 57 , 58 , 64 ), stakeholders offices ( n = 4) ( 47 , 59 , 61 , 66 ), school and stakeholders offices ( n = 2) ( 65 , 67 ), and two studies were conducted online ( 52 , 63 ). The identified papers reported research conducted in 12 countries: the United States ( n = 6) ( 55 , 61 , 63 , 64 , 66 , 67 ), South Korea ( n = 1) ( 48 ), the United Kingdom ( n = 2) ( 49 , 57 ), Sweden ( n = 1) ( 50 ), Ireland ( n = 1)( 51 ), Malaysia ( n = 2) ( 47 , 52 ), Brunei ( n = 1) ( 53 ), Columbia ( n = 1) ( 54 ), Australia ( n = 2) ( 56 , 60 ), Saudi Arabia ( n = 1) ( 39 ), the Netherlands ( n = 1) ( 58 , 59 ), Africa ( n = 1) ( 62 ), and Canada ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…This review draws on the findings of 22 studies with a total of 1,039 participants. Studies have been performed on different settings of healthcare centers ( n = 5) ( 48 , 50 , 55 , 56 , 60 ), schools ( n = 8) ( 39 , 49 , 51 , 53 , 54 , 57 , 58 , 64 ), stakeholders offices ( n = 4) ( 47 , 59 , 61 , 66 ), school and stakeholders offices ( n = 2) ( 65 , 67 ), and two studies were conducted online ( 52 , 63 ). The identified papers reported research conducted in 12 countries: the United States ( n = 6) ( 55 , 61 , 63 , 64 , 66 , 67 ), South Korea ( n = 1) ( 48 ), the United Kingdom ( n = 2) ( 49 , 57 ), Sweden ( n = 1) ( 50 ), Ireland ( n = 1)( 51 ), Malaysia ( n = 2) ( 47 , 52 ), Brunei ( n = 1) ( 53 ), Columbia ( n = 1) ( 54 ), Australia ( n = 2) ( 56 , 60 ), Saudi Arabia ( n = 1) ( 39 ), the Netherlands ( n = 1) ( 58 , 59 ), Africa ( n = 1) ( 62 ), and Canada ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, through appropriate planning and policies, and especially designing programs to increase parental awareness and attitude towards the complications of childhood obesity and methods to prevent it, these barriers can partially be solved. Similar to our study, other studies identified lack of staffing [ 28 ], financial constraints at the implementation level [ 26 , 41 ], and at the family level [ 33 , 42 ] as the barriers to this policy.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, taxing unhealthy foods [ 22 , 23 ], subsidizing some healthy foods [ 22 , 24 ], and using food guide labels on the packages [ 25 ] are among the main recommended strategies. Other suggested strategies to prevent obesity among children and adolescents include: teaching nutritional facts to children and adolescents, holding workshops for parents, supporting intervention policies [ 26 – 28 ], and running social health-related campaigns. For example, a campaign entitled "Say No To Fast Food" was run in Iran in 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the results of a study in Brunei to check the strengths and weaknesses of COP policies through semi-structured interviews with the government and school stakeholders indicated that most stakeholders blamed parents for the problem of childhood obesity. This individualization of the problem from the perspective of stakeholders was identified as a barrier to the planning and implementation of relevant COP interventions [ 15 ]. As far as the researchers investigated, so far, no comprehensive study has been carried out to identify the role of key stakeholders and actors related to COP in Iran.…”
Section: Introductionmentioning
confidence: 99%